Strategi Bersaing Go-Jek Di Tengah Ketatnya Persaingan Moda Transportasi - Arifin, Zainul (Fakultas Ekonomi Universitas Wisnuwardhana, 2018)
Abstract:Go-jek is the company who created services Ojek based online, namely services Ojek ordercan be done through application that readily in download by the user smartphone good android and ios . Competition in business modes of transportation demanding Go-Jek to formulate strategy proper that its position as leader unwavering. Research aims to understand result of formulating strategy to Go-jek.Co.by using the method QSPM. The kind of research it uses a qualitative methodology descriptive from the analysis business development strategy use IFE and EFEmatrix, IEmatrix, training and QSPM matrix. The research results show that Go-Jek are in a position strong in exploit the power of owned and able to overcome the weaknesses that exist, with a total IFE 3,4144 and are being in exploiting the opportunity for existing and address the threat of with a total EFE 2,7234. Keyword: Strategi, IFE, EFE, SWOT, QSPM.